A Dynamic Collusion Analysis Framework Considering Generation and Transmission Systems Maintenance Constraints - Tabatabaei, Mostafa; Setayesh Nazar, Mehrdad; Shafie-khah, Miadreza; Catalão, João P. S. (IEEE, 2020)
Capacity withholding of generation companies is an important issue in market monitoring procedures. The capacity withholding can be intensified in the transmission and generation constrained system. The strategic maintenance of market participants can impose multiple constraints on the system and changes the wholesale electricity market prices. The strategic maintenance of transmission and generation facilities is known as dynamic capacity withholding (DCW) and all of the market-monitoring units need algorithms to detect and reduce DCW. In this paper, a new dynamic capacity withholding index is presented. The method is analyzed on the IEEE 30, 57-bus test system. The numerical results show the effectiveness of the proposed index.
Keywords: Dynamic capacity withholding; Maintenance planning; Transmission system; Strategic Behavior; electricity market; fi=Sähkötekniikka|en=Electrical Engineering|